'Like an Overgrown Garden … ?': Austrian Historical Memory and the Aftermath of Cultural Genocide at a Jewish Cemetery in Vienna. Issue 3 (2nd September 2018) - Corbett, Tim
ABSTRACT: This paper examines the postwar politics of restitution and the related discourses of historical memory and responsibility surrounding a small Jewish cemetery in Vienna, in the eighteenth city district of Währing. A well-tended space and uniquely one of the only surviving Biedermeier-era cemeteries in the city prior to the Holocaust, today it is dangerously dilapidated following extensive desecration and destruction during the Holocaust. Despite its physical neglect and secretive location, this cemetery has become one of the most contested Jewish sites in the present-day Austrian landscape, the focus of intense conflicts over Austrian restitution in the face of its historical responsibility for the crimes of National Socialism. This paper examines the origins of the Währing cemetery's central place in Austrian memory discourses in the first twenty years after the Holocaust, in the context of the re-establishment both of the Austrian Republic and its Jewish community. It thereby explicates the complex relationship emerging between Austrian Jewry and the Austrian state on the one hand, as well as the relationship of both Austrian Jewry and the state to Austria's profound, but largely destroyed Jewish heritage on the other. This paper thus contributes to an understanding of the conflicted ambivalences of both the Austrian state and its Jewish community in the present day by way of examining the reprehensible politics of restitution and memory at this site in the immediate aftermath of the Holocaust.